A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • 4 years ago

How would you go about finding the solution to this system of three equations in 3 variables?

  • This Question is Closed
  1. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    can i see those three equations it might help

  2. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    2x - y + z = 7 x + 2y - 5z = -1 x - y = 6

  3. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    you can probably use the last equation and make x = y + 6 substitute that value into the first or second equation and find y = and then substitue that back into the last equation to get x = i did this 3 years ago in my freshman year but you can try it. If you want i will try to figure this question out and tel you the answer 10 minutes from now? :O

  4. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    its okay, you don't have to work it out hun (:

  5. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    just to be on the safe side :)

  6. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Here it goes: Label all the equations by numbers...gonna be useful 2x - y + x =7 (1) x + 2y - 5z = -1 (2) x - y = 6 (3) find a equation with a coefficient you can eliminate using another equation I chose (1) and (2) Make one variable have the same coefficient Since the third equation consist only of x and y --> we need to eliminate z in this one 2x - y + z = 7 (1) x 5 x + 2y -5z = -1 (2) 10x - 5y + 5z = 35 + x + 2y -5z = -1 ------------------- 11x - 3y = 34 Now that you made an equation consisting of x and y: solve for one variable using substitution or elimination rearrange (3) x - y = 6 x = y + 6 substitute x = y - 6 into 11x - 3y = 34 11x - 3y = 34 11(y + 6) - 3y = 34 11y + 66 - 3y = 34 * combine the like terms and move 66 to the right side 11y - 3y = 34 - 66 8y = -32 * Divide both sides by 8 y = -4 one variable down two more to go substitute y = -4 into (3). Make sure you use the original equation and not the re arranged one :D x - y = 6 x - (-4) = 6 x + 4 = 6 * Move 4 over to the other side x = 6 - 4 x = 2 Alright now you got two variables and you need the last one :D substitute x = 2 and y = -4 into equation (2) 2x - y + z = 7 (2) 2(2) - (-4) + z = 7 4 + 4 + z = 7 8 + z = 7 z = 7 - 8 z = -1 You got all three variables. Write your therefore statement. Therefore, x = 2, y = 4 and z = -1 Moral of the question: the order matters

  7. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thank you (:

  8. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.